CHANGES OF THE HEART RATE VARIABILITY IN THE PATIENTS WITH ISCHEMIC HEART DISEASE AND CHRONIC HEART FAILURE DURING SESSION OF HYPERBARIC OXYGENATION THERAPY - Stepanov, A.V.; Yabluchansky, N.I.; Stepanova, S.V.; Avchinnikova, T.A.; Kartvelishvily, A.Yu. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The results of the heart rate variability study during sessions of hyperbaric oxygenation therapy (HBOT) for the patients with ischemic heart disease and chronic heart failure demonstrated in the article. The protocol of HBOT is: 1,4 ata, 60 min. Significant increase under HBOT of the total power, parasympathetic activity and decrease the sympathetic activity was obtained. We hypotized that the values of the heart rate variability changes strongly depend from the pressure in the chamber, hyperoxya and horizontal posture of the patient.